3 - k - 5k =3
i need help on this asap
2 answers:
Hello there!
3-k-5k=3
Combine like terms:
3-6k=3
-6k=3-3
-6k=0
k=0
Hope it helps!
~Just a determined gal
#CarryOnLearning
Answer:
k = 0
Step - By - Step:
1. 3 - k - 5k = 3
3 - 6k =3
2. rearrange terms:
3 - 6k = 3
-6k + 3 = 3
3. Subtract 3 from both sides of the equation:
-6k_3=3
-6k+3-3=3-3
4. simplify:
-6k + 3 - 3 = 3 - 3
-6k = 3 - 3
-6k = 0
5. divide both sides of the equation by the same term:
-6k = 0
-6k/-6 = 0/-6
6. simplify:
k = 0/-6
You might be interested in
Answer:
Never
Step-by-step explanation:
Adding together an obtuse angle (greater than 90°) and acute angle (less than 90°) should result in an obtuse angle every time
Washington: 117 Hits
Sanchez: 93 Hits
Hope this helps, have a nice day!
Answer:
Angle 1 is 60°
Step-by-step explanation:
Answer:
Ray DC and Ray DE
Step-by-step explanation: